Chemical-physical and ecological characterisation in the environmental project of a polluted coastal area: the Bagnoli case study - BERGAMIN, I.; ROMANO, E.; GABELLINI, M.; AUSILI, A.; CARBONI, M.G. (Mediterranean Marine Science, 2003)
The Bagnoli Bay (southern Tyrrhenian Sea, Naples, Italy) has been impacted for about one century by heavy anthropogenic pollution due to an important steel plant. A multidisciplinary environmental research, aimed at the reclamation of the marine contaminated area, was planned in order to evaluate, through quantitative data, the chemical-physical and ecological characteristics of marine sediments; the latter ones are strictly related to the composition and structure of benthic foraminiferal assemblages. A comprehensive statistical approach, considering all data, was attempted in order to single out the influence of pollutants on the single species distribution. The results show strong heavy metal pollution (Fe, Mn, Pb and Zn) in the vicinity of the industrial plant. Many foraminiferal species (Haynesina germanica, Miliolinella subrotunda,Quinqueloculina parvula), have a good tolerance to some trace metals while, Bulimina sublimbata, Elphidiummacellum and Miliolinella dilatata show a good tolerance to PAHs pollution.